Analysis of snake venom metalloproteinases from Myanmar Russell's viper transcriptome. (May 2018) - Yee, Khin Than; Tongsima, Sissades; Vasieva, Olga; Ngamphiw, Chumpol; Wilantho, Alisa; Wilkinson, Mark C.; Somparn, Poorichya; Pisitkun, Trairak; Rojnuckarin, Ponlapat
Abstract: Snake venom metalloproteinases (SVMPs) are the key enzymes in Russell's viper (RV) venom which target all important components of haemostasis, such as clotting factors, platelets, endothelial cells and basement membrane. The structural diversity of SVMPs contributes to the broad spectrum of biological activities. The aim of the study was to investigate the SVMP transcript profile to gain better insights into the characteristic clinical manifestations of the Myanmar Russell's viper (MRV) bites that distinguish it from the RVs of other habitats. Next generation sequencing (RNA-Seq) of mRNA from MRV venom glands (2 males and 1 female) was performed on an Illumina HiSeq2000 platform and then de novo assembled using Trinity software. A total of 59 SVMP contigs were annotated through a Blastn search against the serpent nucleotide database from NCBI. Among them, disintegrins were the most abundant transcripts (75%) followed by the P-III class SVMPs (25%). The P-II SVMPs were scarce (0.002%), while no P-I SVMPs were detectable in the transcriptome. For detailed structural analysis, contigs were conceptually translated and compared with amino acid sequences from other RVs and other vipers using Clustal Omega. The RTS-disintegrin (jerdostatin homolog) was the most abundant among transcripts corresponding to 5 disintegrin isoforms. From 10 isoforms of SVMPs, RVV-X, and Vipera lebetina apoptosis-inducing protease (VLAIP) homolog, hereby termed Daboia siamensis AIP (DSAIP), were found to be highly expressed. Venom protein analysis using SDS-PAGE followed by mass spectrometry revealed that the disintegrin was scarce, while the latter two SVMPs were abundant. These two proteins can contribute to severe clinical manifestations caused by MRV envenomation. Highlights: The most abundant toxin transcripts in the Myanmar Russell's viper transcriptome were annotated as metalloproteinases. Disintegrin transcripts were the most abundant transcripts (75%) followed by P-III SVMPs (25%). Five isoforms of disintegrins and 10 isoforms of SVMPs were identified in the current transcriptomes. Protein analysis revealed that the disintegrin was scarce, while the P-III SVMPs were abundant. The highly-expressed P-III SVMPs were RVV-X and the novel Vipera lebetina apoptosis-inducing protease (VLAIP) homolog.